Unemployment in chronic airflow obstruction around the world: results from the BOLD study. Issue 3 (21st September 2017) - Grønseth, Rune; Erdal, Marta; Tan, Wan C.; Obaseki, Daniel O.; Amaral, Andre F.S.; Gislason, Thorarinn; Juvekar, Sanjay K.; Koul, Parvaiz A.; Studnicka, Michael; Salvi, Sundeep; Burney, Peter; Buist, A. Sonia; et al.
We aimed to examine associations between chronic airflow obstruction (CAO) and unemployment across the world. Cross-sectional data from 26 sites in the Burden of Obstructive Lung Disease (BOLD) study were used to analyse effects of CAO on unemployment. Odds ratios for unemployment in subjects aged 40–65 years were estimated using a multilevel mixed-effects generalised linear model with study site as random effect. Site-by-site heterogeneity was assessed using individual participant data meta-analyses. Out of 18 710 participants, 11.3% had CAO. The ratio of unemployed subjects with CAO divided by subjects without CAO showed large site discrepancies, although these were no longer significant after adjusting for age, sex, smoking and education. The site-adjusted odds ratio (95% CI) for unemployment was 1.79 (1.41–2.27) for CAO cases, decreasing to 1.43 (1.14–1.79) after adjusting for sociodemographic factors, comorbidities and forced vital capacity. Of other covariates that were associated with unemployment, age and education were important risk factors in high-income sites (4.02 (3.53–4.57) and 3.86 (2.80–5.30), respectively), while female sex was important in low- to middle-income sites (3.23 (2.66–3.91)). In the global BOLD study, CAO was associated with increased levels of unemployment, even after adjusting for sociodemographic factors, comorbidities and lung function. Chronic airflow obstruction increases risk of unemployment, and is a burden to welfare systems worldwide http://ow.ly/cxzv30cQ17A